The lord of the rings The return of the king : Visual companion - Fisher, Jude; Tolkien, J. R. R. 1892-1973. (Boston ; New York : Houghton Mifflin, 2003)
A companion guide to the third film features lavish spreads and follows the journeys of Frodo, Sam, and Gollum as they slowly make their way into the depths of Mordor, and traces the efforts of the scattered Fellowship members, who journey to Minas Tirith for a final stand against the forces of Sauron. Movie tie-in. 150,000 first printing.
Ill. on lining papers.
At head of title on cover: The official illustrated movie companion.
Keywords: Tolkien, J. R. R. -- 1892-1973.; Middle Earth (Imaginary place); Fantasy fiction, English